Endometriosis-Related Infertility: The Role of the Assisted Reproductive Technologies. (9th July 2015) - Surrey, Eric S.
Abstract : The assisted reproductive technologies, particularly in vitro fertilization (IVF), represent the most efficient and successful means of overcoming infertility associated with endometriosis. Although older studies suggest that IVF outcomes are compromised in endometriosis patients, more contemporary reports show no differences compared to controls. The exception may be evidence of poorer outcomes and diminished ovarian response in women with advanced disease, particularly those with significant ovarian involvement or prior ovarian surgery. Prolonged pre-IVF cycle suppressive medical therapy, particularly gonadotropin releasing hormone agonists, appears to improve success rates in a subset of endometriosis patients. However, as of yet, there is no diagnostic marker to specifically identify those who would most benefit from this approach. Pre-IVF cycle surgical resection of nonovarian disease has not been consistently shown to improve outcomes with the possible exception of resection of deeply invasive disease, although the data is limited. Precycle resection of ovarian endometriomas does not have benefit and should only be performed for gynecologic indications. Indeed, there is a large body of evidence to suggest that this procedure may have a deleterious impact on ovarian reserve and response. A dearth of appropriately designed trials makes development of definitive treatment paradigms challenging.